2016
DOI: 10.1016/j.jhsa.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

National Utilization Patterns of Steroid Injection and Operative Intervention for Treatment of Common Hand Conditions

Abstract: Purpose To conduct a population-level analysis of practice trends and probability of surgery based on the number of steroid injections for common hand conditions. Methods Patients at least 18 years old receiving injection or surgery for carpal tunnel syndrome (CTS), trigger finger (TF), or De Quervain tenovaginitis (DQ) were identified for inclusion using the 2009–2013 Truven MarketScan databases. The number of injections performed was counted, and time between injection and operation was calculated for pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…19 This was consistent with a national database study assessing 102,778 records for treatments of trigger fingers finding that only 16% of which received at least 3 injections. 20 Based on a presumed minimal chance of third injection to prevent surgery, a cost-minimization analysis by Kerrigan et al determined that the optimal treatment strategy for recurrent trigger finger was two steroid injections followed by surgery. 21 This same analysis found that the third injections would have to provide ≥9% of patients with long term relief to be the most cost-effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 This was consistent with a national database study assessing 102,778 records for treatments of trigger fingers finding that only 16% of which received at least 3 injections. 20 Based on a presumed minimal chance of third injection to prevent surgery, a cost-minimization analysis by Kerrigan et al determined that the optimal treatment strategy for recurrent trigger finger was two steroid injections followed by surgery. 21 This same analysis found that the third injections would have to provide ≥9% of patients with long term relief to be the most cost-effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of patients that received 2 corticosteroid injections, 26% required surgery, compared with 16% in our series. 16 Previous studies of nodular versus synovitic variants of trigger digit indicated increased injection efficacy with corticosteroid for nodular trigger digits. 3 Other studies have failed to demonstrate a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these studies suggest that if noninvasive treatments including splinting, physical therapy, oral medications, and topical medications fail to resolve symptoms, a single peri‐tendinous injection with corticosteroid may provide benefit. Although no studies exist to clearly characterize practice patterns of CSI versus noninjection therapy for de Quervain tenosynovitis in the United States, the treatment is common, and one review has suggested that patients who receive CSI therapy have only 12% odds of undergoing subsequent surgical intervention [24]. Ultrasound‐guided injection may improve identification of clinically meaningful anatomic variants of the APL and EPB extensor tendon sheath [25] and may improve placement of injectate [24] during treatment of de Quervain tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies exist to clearly characterize practice patterns of CSI versus noninjection therapy for de Quervain tenosynovitis in the United States, the treatment is common, and one review has suggested that patients who receive CSI therapy have only 12% odds of undergoing subsequent surgical intervention [24]. Ultrasound‐guided injection may improve identification of clinically meaningful anatomic variants of the APL and EPB extensor tendon sheath [25] and may improve placement of injectate [24] during treatment of de Quervain tenosynovitis. The current case, however, suggests that dermal complications of CSIs are still a notable risk despite visual image guidance with verification of nondermal and non−intra‐articular placement of the injectate.…”
Section: Discussionmentioning
confidence: 99%